Subjective earnings and academic expectations of tertiary education in Colombia (2018)
We analysed the academic expectations and earning expectations of a nationally representative sample of Colombian students who were finishing their upper-secondary education (high school) and considering three potential scenarios: whether to finish their studies, enrol in a vocational career, or pursue a college degree. We found that these students’ earning expectations are correlated with local labour market wages. However, they expect earnings as university graduates that are significantly above the current observed earnings, which is not the case for the other two levels of education. We also found that earning and academic expectations (test scores and odds of attending college) are closely related to their family socioeconomic background, school and municipality characteristics, and even reflect aspects such as gender gaps or private school premiums. Finally, both academic and earnings expectations are related to actual realised test scores. © 2018, Banco de la Republica. All rights reserved.